Textbook of hand eczema - Lachapelle, Jean-Marie; Maibach, Howard I.; Alikhan, Ali (Springer Berlin Heidelberg, 2014)
Hand eczema is a major complaint worldwide and a frequent occupational disorder. This book provides a comprehensive and detailed overview of the classification, etiology, diagnosis, prevention, and therapy of hand eczema. It is innovative, up to date, and practical. The links with particular occupations are explained, the various diagnostic tests are presented, and the role of different topical and systemic treatments is clearly described. The authors are world leaders in the field. The Textbook of Hand Eczema reflects a new era in hand dermatitis and will be invaluable for all who deal with the condition in their clinical practice.